Carbon stock and dynamics in a managed forest in Central Amazon - Souza, Cíntia Rodrigues de; Azevedo, Celso Paulo de; Rossi, Luiz Marcelo Brum; Santos, Joaquim dos; Higuchi, Niro (Scientia Forestalis/Forest Sciences, 2018)
The Amazon forest has been in evidence in global discussions about their role in control of global climate change, both by the ability to emit greenhouse gases into the atmosphere via burning or thinning, how to absorb carbon from the atmosphere by through the growth of the stand. This study analyzed data from a forest managed in 1987, in Manaus/AM. This work aimed to study the carbon stock and dynamics. The forest inventories were conducted in 15 hectares of permanent plots. The average rates of recruitment were 4.9%, 4.8%, 3.7% and 5% for control treatments and logging of 1/3, 1/2 and 2/3, respectively, and the average mortality rates were 3.1%, 6%, 4.8% and 6.7%, for control treatments and logging of 1/3, 1/2 and 2/3, respectively. The basal area (23.1 m2 ha-1 in 2005, 23.6 m2 ha-1 in 2007 and 23.7 m2 ha-1 in 2010), the volume (345 m3 ha-1 in 2005, 351.3 m3 ha-1 in 2007 and 353.7 m3 ha-1 in 2010) and the carbon content (149.2 t ha-1 in 2005, 151.8 t ha-1 in 2007 and 152.6 t ha-1 in 2010) increased in all measurements. However, the statistical difference between these values was not significant, so it was concluded that the forest was in equilibrium with the atmosphere during the period evaluated. A comparison of the carbon stock of the years measured with the stock pre-exploratory, in 1986, showed that in 2010 the carbon stock equaled the content before logging, meaning the forest recovery. © 2018 University of Sao Paolo. All rights reserved.
Keywords: Biomass; Carbon; Climate Change; Dynamics; Greenhouse Gases; Climatic Changes; Control Treatments; Forest Dynamics; Forest Inventory; Forest Recovery; Global Climate Changes; Permanent Plot; Statistical Differences; Forestry